Hydrochemical Evolution in Ciliwung River – Java, Indonesia: Study of Sea Water Mixture and Mineral Dissolution - Evarista Ristin Pujiindiyati; Paston Sidauruk; Tantowi Eko Prayogi; Faizal Abdillah (Indonesian Journal of Chemistry, 2020)
The chemical characteristics of the Ciliwung River were analyzed to understand hydrochemical evolution. A fraction of sea water mixture and kinds of mineral controlling for chemicals were also determined. During three year investigations in 2015, 2016, and 2018, electrical conductivity increased with decreasing elevations. Two hydrochemical facies had been identified for the Ciliwung river water; those were Ca-Mg-HCO3 and Ca-Na-HCO3.  The river water mixing with seawater was recognized in the Mangga Dua site in which its water type had shifted to Na-Ca-HCO3-Cl. Based on Na-Cl contents, the fraction of sea water into the Ciliwung River reached 2% in the Mangga Dua site during the dry season and decreased to 0.7% during the rainy season in 2015. The much higher monthly rainfall during the dry season in 2016 and 2018 had washed out invading seawater from the Mangga Dua site; its fraction of sea water was less than 0.4%. Saturation indexes with respect to calcite, dolomite, and gypsum minerals showed an increasing trend related to the decreasing elevations. All water samples were undersaturated with respect to gypsum. Meanwhile, saturation indexes with respect to calcite and dolomite mostly indicated undersaturated, except in the Mangga Dua site that was saturated (during the rainy season in 2015 and dry season in 2018) and supersaturated during the dry season in 2015.